2013
DOI: 10.1111/een.12065
|View full text |Cite
|
Sign up to set email alerts
|

Age‐specific maternal effects interact with larval food supply to modulate life history in Coleomegilla maculata

Abstract: 1. Maternal effects can modify progeny phenotypes to improve their survival under variable conditions, such as changes in food supply. In aphidophagous coccinellids, maternal effects can influence egg size, developmental rate, and final adult body size.2. Four cohorts of Coleomegilla maculata De Geer larvae were reared from four different points in their mothers' reproductive lives (1st, 12th, 24th, and 36th oviposition days) and divided into two diet treatments for rearing; 30-min daily access to eggs of Ephe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Along with external environmental cues, intrinsic characteristics of the mother may also influence offspring fitness (Vargas, Michaud, Nechols, & Moreno, 2014). In many species, maternal age results in shifts in the relationship between early reproduction and life span, where older mothers produce offspring that maximize early reproduction at the expense of life span (Marshall, Heppell, Munch, & Warner, 2010;Metcalfe & Monaghan, 2001).…”
mentioning
confidence: 99%
“…Along with external environmental cues, intrinsic characteristics of the mother may also influence offspring fitness (Vargas, Michaud, Nechols, & Moreno, 2014). In many species, maternal age results in shifts in the relationship between early reproduction and life span, where older mothers produce offspring that maximize early reproduction at the expense of life span (Marshall, Heppell, Munch, & Warner, 2010;Metcalfe & Monaghan, 2001).…”
mentioning
confidence: 99%
“…Thus, another transgenerational impact of ablation/regeneration was positive, again contradicting our initial hypothesis. Coccinellids are known to exert maternal and paternal effects on their progeny, probably to raise their own fitness (Vargas et al., ,, ; Mirhosseini et al., ). If limb regeneration in H. axyridis cues an epigenetic cascade that involves the activation of many genes, some could be responsible for pleiotropic enhancement of parental effects.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that processes associated with the recovery from ablation and limb regeneration would require the up‐regulation of many developmental genes in the pupal stage, with the potential for a cascade of secondary effects on subsequent physiology and life history. As parental effects in coccinellids are quite sensitive to parental condition (e.g., Vargas et al., ,, , ), we also hypothesized that physiological and pleiotropic effects associated with regeneration would be transgenerational and that regenerative costs would be evident in the life histories of progeny.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The recorded effect of maternal origin on the ability of H. variegata larvae to survive on a pollen diet calls for further investigation to determine the cause of this variation among egg batches. For example, Vargas et al 24 found that maternal age affected the number of larval instars before pupation in Coleomegilla maculata (DeGeer); larvae from later-hatching progeny were more likely to pupate quicker, giving them an advantage when aphid populations are in decline. The recorded variation in H. variegata larval survival on pollen may be determined genetically or through maternal effects.…”
Section: Discussionmentioning
confidence: 99%